2004
DOI: 10.1007/bf03018394
|View full text |Cite
|
Sign up to set email alerts
|

L’index «A-line ARX» peut être un détecteur plus sensible du réveil que l’index bispectral pendant l’anesthésie avec propofol-fentanyl-protoxyde d’azote: une recherche préliminaire

Abstract: P Pu ur rp po os se e: : To compare changes in the A-line ARX index (AAI) by the Alaris AEP monitor™ with those of the bispectral index (BIS) during propofol-fentanyl-nitrous oxide anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Generally, it is considered that AAI 60-100 represents the normal waking state, 40-60 represents the sleep state, 30-40 represents the light anesthesia state, <30 represents the clinical anesthesia state and <10 represents the deep anesthesia state (22). It has been suggested that AAI can much more sensitively reflect the depth of anesthesia than the bispectral index in Pro-fentanyl anesthesia (23). The present study showed that the AAI of group A at T1 was decreased compared with that at T0 (P<0.05), and those of groups B, C and D at T1 were significantly lower than those at T0 (P<0.01); those of groups D and E at T3 were significantly increased compared with those at T2 (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it is considered that AAI 60-100 represents the normal waking state, 40-60 represents the sleep state, 30-40 represents the light anesthesia state, <30 represents the clinical anesthesia state and <10 represents the deep anesthesia state (22). It has been suggested that AAI can much more sensitively reflect the depth of anesthesia than the bispectral index in Pro-fentanyl anesthesia (23). The present study showed that the AAI of group A at T1 was decreased compared with that at T0 (P<0.05), and those of groups B, C and D at T1 were significantly lower than those at T0 (P<0.01); those of groups D and E at T3 were significantly increased compared with those at T2 (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Kurita [9] and Nishiyama [10] found that the MLA was able to predict movement following surgical incision and the insertion of a laryngeal mask, whereas BIS could not do this. These authors considered that this difference in the response occurred because BIS measures cortical and not subcortical activity, whereas MLAEP does reflect subcortical activity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the ability of BIS and MLAEP to detect stimuli during anaesthesia for surgical operations, with conflicting results [9][10][11][12]. However, there are very few studies that have performed this evaluation in critically ill adults [13][14][15], and only one that has studied the use of BIS and the COMFORT scale following tracheal suctioning in critically ill children [16].…”
mentioning
confidence: 99%
“…Anaesthetics or sedation alters EEG latency and amplitude (Drummond 2000;Thornton and Sharpe 1998) and these changes are used to generate the A-line ARX Index TM (AAI) (Mantzaridis and Kenny 1997). BIS and AAI have a range from zero, where patient's EEG is isoelectric, to 100, when patients are awake (Nishiyama and Hanaoka 2004;Rampil 1998). To achieve desired levels of anaesthesia or sedation, medications can be titrated according to the displayed index.…”
Section: Norwood Usa) and Alaris Auditory Evoked Potentials (Aep) Momentioning
confidence: 99%